Antihelmintic Drugs: A Comprehensive Review of Methods of Synthesis and Mechanism - Tripathi, Adya; Rajendiran, A; Bhadauriya, Himanshi; Singh, Anju (Journal of Neonatal Surgery, 2025)
Antihelmintic drugs are essential in the treatment of parasitic worm infestations, which remain a significant public health challenge worldwide. These drugs target various stages of the helminth lifecycle, including larval, adult, and egg stages, helping to reduce the burden of parasitic diseases such as ascariasis, schistosomiasis, and strongyloidiasis. This comprehensive review examines the different classes of antihelmintic agents, focusing on their methods of synthesis and mechanisms of action. The major categories include Benzimidazoles, macrocyclic lactones, imidazothiazoles, and others, each with distinct synthetic routes and modes of action. Benzimidazoles, such as Albendazole and Mebendazole, are synthesized using a combination of condensation and cyclization reactions, targeting microtubule polymerization to disrupt helminth cell division. Macrocyclic lactones, including Ivermectin, are derived from fermentation processes, and they inhibit neuromuscular transmission by binding to glutamate-gated chloride channels. Imidazothiazoles, like levamisole, act on nicotinic acetylcholine receptors, leading to paralysis and expulsion of the parasite. The review also discusses emerging antihelmintic agents, including those derived from natural sources, and the challenges associated with resistance development. Understanding the synthesis, mechanism of action, and potential resistance mechanisms is vital for the continued advancement of antihelmintic therapy. This review provides insights into current trends and future directions for the design of more effective and sustainable antihelmintic drugs.